2022
DOI: 10.1002/jcph.2007
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the Pediatric Dosing Recommendations for Unfractionated Heparin Using Real‐World Data: A Pharmacokinetic–Pharmacodynamic Modeling Approach

Abstract: Optimal pediatric dosing of unfractionated heparin (UFH) is challenging because of the paucity of clinical outcome and pharmacokineticpharmacodynamic (PK/PD) studies in pediatrics. This study aimed to: (i) develop a PK/PD model for UFH, quantified by anti-factor Xa assay, and the UFH effect, measured by activated partial thromboplastin time (aPTT); and (ii) use simulations to evaluate pediatric UFH infusions for achieving the anti-factor Xa (0.3-0.7 IU/mL) therapeutic target. Electronic health record data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…20 The estimated typical steady-state CL value was consistent between ECMO and non-ECMO settings. 25,26,29,30 However, the consistency between CL under ECMO and non-ECMO conditions contradicts with a prior ECMO study in infants (n = 5), where UFH CL was approximately doubled during the ECMO session compared to after the decannulation procedure. 12 Considering the physicochemical properties, heparin is a hydrophilic drug that reduces the susceptibility of sequestration by ECMO circuits.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…20 The estimated typical steady-state CL value was consistent between ECMO and non-ECMO settings. 25,26,29,30 However, the consistency between CL under ECMO and non-ECMO conditions contradicts with a prior ECMO study in infants (n = 5), where UFH CL was approximately doubled during the ECMO session compared to after the decannulation procedure. 12 Considering the physicochemical properties, heparin is a hydrophilic drug that reduces the susceptibility of sequestration by ECMO circuits.…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, the recommendations from the study are similar to the published American College of Chest Physicians guidelines on the UFH starting infusion in non-ECMO pediatric patients (28 IU/h/kg for patients aged 1 year or younger and 20 IU/h/kg for patients aged older than 1 year), although some recent studies suggested starting infusions up to 33 IU/h/kg for younger children. 14,18,30,37 The proposed dose titration schemes (regimens 3, 4, and 5) were efficient in terms of increasing the percentage of patients within the antifactor Xa therapeutic target and lowering the percentage above the target compared to the current hospital protocol. Regimens 3 and 4 could be more practical for implementation given the complexity of regimen 5 in terms of dose adjustments based on the timing on ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to perform a PK analysis of UFH in adult VA-ECMO patients using a nonlinear mixed-effects modeling approach. Among the previous studies that investigated UFH PK [ 18 , 19 , 20 , 21 , 22 , 23 ], only a few focused on cardiopulmonary bypass (CPB) [ 21 , 22 ] or ECMO [ 23 ]. Similar analyses were performed in adult patients undergoing CPB for cardiac surgery, using either anti-activated factor II (anti-IIa) [ 21 ] or anti-Xa [ 22 ] assays.…”
Section: Discussionmentioning
confidence: 99%
“…Different absorption and disposition structural PK models were explored to fit NHC concentration time profiles as described previously [16] . Log-normal distribution was used to describe inter-individual variabilities (IIV) on PK parameters and multiple residual error models such as additive, proportional and combined error models were tried to describe the data [17] .…”
Section: Methodsmentioning
confidence: 99%